Effects of polychlorinated biphenyls on metamorphosis of a marine fish Japanese flounder (Paralichthys olivaceus) in relation to thyroid disruption. Issue 1 (15th June 2017) - Dong, Yifei; Zhang, Xiaona; Tian, Hua; Li, Xiang; Wang, Wei; Ru, Shaoguo
Abstract: This study examined the influence of environmental concentrations of Aroclor 1254 (10, 100, and 1000 ng/L) on metamorphosis of Paralichthys olivaceus, and analyzed the mechanisms in relation to thyroid disruption. Results showed that 100 and 1000 ng/L Aroclor 1254 delayed metamorphosis and that 1000 ng/L Aroclor 1254 caused abnormal morphology. Thyroxine and triiodothyronine levels in the control group were significantly elevated at metamorphic climax, but treatment with 100 and 1000 ng/L delayed the increase in thyroid hormones (THs) and retarded metamorphic processes. In larvae exposed to 1000 ng/L Aroclor 1254, TH levels at metamorphic climax were significantly lower than those of the control group at the same metamorphic stage. We suggest that the effects of Aroclor 1254 on larval metamorphosis can be explained by disruption of thyroid homeostasis. These findings provide a new perspective and biological model for thyroid-disrupting chemicals (TDCs) screening and investigating interference of thyroid function by TDCs. Highlights: Aroclor 1254 retarded metamorphic processes of Paralichthys olivaceus . Aroclor 1254 delayed the increase in THs at metamorphic climax of P. olivaceus . Inhibition of Aroclor 1254 on metamorphosis was related to lower T4 and T3 levels. P. olivaceus provides a good model for studying interference of thyroid function.